2005
DOI: 10.1159/000087354
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fish Antigens Aerosolized during Fish Processing Using Newly Developed Immunoassays

Abstract: Background: Aerosolization of fish proteins during seafood processing has been identified as a potential route for allergic sensitization and occupational asthma among workers involved in high-risk activities. The aim of this study was to develop immunological assays for the quantification of aerosolized fish antigens in a fish-processing factory. Methods: Polyclonal antibodies to the main fish species processed in the factory (anchovy and pilchard) were generated in rabbits and compared by ELISA inhibition as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…This allowed to detect parvalbumins with high sensitivity and accuracy in the samples. Previously, it has been shown that the use of non-species-specific antibodies carries pitfalls [12,14,15]. In this study, the calibration curves clearly demonstrate a difference in antibody sensitivity (fig.…”
Section: Discussionsupporting
confidence: 54%
“…This allowed to detect parvalbumins with high sensitivity and accuracy in the samples. Previously, it has been shown that the use of non-species-specific antibodies carries pitfalls [12,14,15]. In this study, the calibration curves clearly demonstrate a difference in antibody sensitivity (fig.…”
Section: Discussionsupporting
confidence: 54%
“…The sensitive ELISA method used to measure tropomyosin (Kamath et al 2014;Malo et al 1997) has no unspecific binding to other proteins and no loss of binding due to protein modification procedures that may have influenced the levels reported in other studies (Griffin P 1994;Lopata and Jeebhay 2013;Lopata et al 2005). Previous studies have also used the highly sensitive mass spectrometric based strategies to quantify tropomyosin and arginine kinase (Rosmilah et al 2012;Abdel Rahman, Gagne, and Helleur 2012;Abdel Rahman et al 2011;Abdel Rahman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The antigenicity of a protein is not necessarily like its allergenicity; however, IgG-antibodies are useful to develop immunoassays for the detection of food allergens. Polyclonal antibodies against canned pilchard and fresh anchovy were produced to develop an inhibition enzyme-linked immunosorbent assay (ELISA) for the detection of aerosolized fish antigens (Lopata et al, 2005). The assay sensitivity was 0.5 mg/mL in phosphate-buffered saline/0.05% Tween-20 extracts of environmental air samples correlating to a 105-ng/m 3 aerosol concentration.…”
Section: Analytical Methods For the Detection Of Fish In Foodsmentioning
confidence: 99%
“…However, if fish allergen is inhaled (e.g., in the vapor from boiling fish or in the air at a fish market), symptoms of asthma and even generalized anaphylactic symptoms may develop (Crespo et al, 1995;. In fish-processing workplaces, occupational exposure to fish allergens can induce the typical IgE-mediated hypersensitive systemic, cutaneous, gastrointestinal, and respiratory reactions (Douglas et al, 1995;Rodr ıguez et al, 1997;Sicherer et al, 2000;Lopata et al, 2005).…”
Section: Routes Of Exposurementioning
confidence: 99%